Design of a prototype of hand orthosis with pneumatic actuators - Tortós-Vinocour, Pablo Enrique (2020)
In Costa Rica, there has been an increasing need for prosthetic and orthotic devices in the last years, especially in populations with diabetes, cerebral palsy, and people over 65 years old, some of the devices are developed in the country, however, others such as hand orthoses are rarely produced in the region. The use of soft robotics in the replica of human movement has been growing. By considering the work done by Deimel and Brock[3] and the Simulation Bioengineering Laboratory(SIBILA) it  is intended to develop a soft hand orthosis for a patient with cerebral palsy, who has problems grasping objects with his right hand. This project aims to improve grip strength and finger position for the patient. The project is divided in 3 parts: replica of the patient’s hand, elaboration of pneumatic muscles and the elaboration of a voice control system. The result is a pneumatic actuation that allows to grip objects with different shapes and gives strength to the fingers, in addition to this, the orthosis fits the model of the patient’s hand. In conclusion, it is recommended to optimize the design of the muscles with a silicone that is more resistant and a thicker reinforcement helix. Also, it is recommended to start carrying out the tests of the orthosis with the model of the hand inside it.